2007
DOI: 10.1007/s10995-007-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Seat Belt use, Counseling and Motor-Vehicle Injury During Pregnancy: Results from a Multi-State Population-Based Survey

Abstract: Based on PRAMS, it is estimated that about 92,500 pregnant women are hurt annually in motor-vehicle crashes in the United States. Despite this reported risk and the proven efficacy of restraint use, most pregnant women do not report being counseled about seat belt use during prenatal visits. Limitations of PRAMS methodology make it difficult to determine the association of prenatal counseling with seat belt use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Studies that have examined prenatal health education often model it as a predictor rather than an outcome on its own or focus on a selected health topic . In addition, although disparities in adverse birth outcomes are well known with racial or ethnic minorities and socioeconomically disadvantaged groups having higher risks for these events, few studies have examined disparities in the receipt of prenatal health education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have examined prenatal health education often model it as a predictor rather than an outcome on its own or focus on a selected health topic . In addition, although disparities in adverse birth outcomes are well known with racial or ethnic minorities and socioeconomically disadvantaged groups having higher risks for these events, few studies have examined disparities in the receipt of prenatal health education.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Studies that have examined prenatal health education often model it as a predictor rather than an outcome on its own [14][15][16] or focus on a selected health topic. 14,17 In addition, although disparities in adverse birth outcomes are well known with racial or ethnic minorities and socioeconomically disadvantaged groups having higher risks for these events, [18][19][20][21] few studies have examined disparities in the receipt of prenatal health education. One study examined the racial variations in receipt of advice from health care practitioners during pregnancy using data drawn from the 1988 National Maternal and Infant Health Survey.…”
Section: Introductionmentioning
confidence: 99%
“…These figures are consistent with those reported in the USA after taking into account the slippery roads in winter due to heavy snowfall in Sapporo. The estimated risk of pregnant women being injured in MVA is 2.3%, and that of being a driver in MVA is 1.3% in North Carolina, USA . Although no information was collected regarding maternal or fetal injuries due to MVA in this study, severe injuries were considered to be uncommon based on findings in other countries; visits to an emergency department following MVA occurred in approximately 6.5 per 1000 pregnant women in Canada, while in Australia, admission to hospital following MVA occurred in 3.5 per 1000 pregnant women .…”
Section: Discussionmentioning
confidence: 88%
“…12, 49, 50, 52, 54 A multi-state study conducted across 22 states found that the prevalence of reported prenatal counseling about belt use ranged from 38% (Arkansas) to 59% (Washington State). 12 This range is consistent with the findings from several prenatal clinic-based studies. For example, in Michigan, approximately 55% of women who completed a survey at two prenatal visits (n=298) reported that they received information about belt use from their health care provider.…”
Section: Motor Vehicle Safety Interventionsmentioning
confidence: 99%